A TWINNING STUDY IN IRAN - DD. Farhud; GR.Walizadeh; MS. Kamali; H. Malek Afzali (Tehran University of Medical Sciences, 1986)
Three hundred twin births from a hospital in Tehran, Iran have been analyzed for seasonal variation at birth and physical measurements. The results show that the highest twinning rates for MM (5.61), FF (7.73) and MF (5.36) were seen in April, January and September, respectively. The four physical measurements at birth showed non-significant differences among the male and female twins, but MM and M twins showed higher physical measurements compared with those of FF and F twins. Mean weight was 2441.14 (MM), 2467.29 (M), 2391.45 (FF) and 2424.38 (F) ; that of the stature was 47.40 (MM), 47.36(M), 46.78(FF) and 46.26(F); that of head circumference was 32.40 (MM), 32.30(M), 32.11(FF) and 30.64(F); and finally that of the chest girth was 29.61 (MM), 29.84(M), 29.01(FF) and 29.30(F).